Performance of solid waste by product (palm oil clinker) as partial coarse aggregate replacement - A. Razak, Mustapha (2017)
This research describes experimental studies on the effects of substitution of POC aggregates towards the mechanical properties of concrete which consist of workability, compressive strength and flexural strength. The most suitable water cement ratio for the mixture was obtained through trial mixtures and yielded a constant of 0.53. The different percentage of POC was use as partial coarse aggregate replacement which is consist of 0%, 5%, 10%, and 15% replacement by volume of granite. All of the testing were followed the British standard. The workability of concrete were tested by using slump test to check the consistency of freshly made concrete. For compressive strength, total of 36 cubes with size 150mm x 150mm x 150mm were used to determine the compressive strength of concrete when replace with 0%, 5%, 10% and 15% of POC as a replacement of coarse aggregates in concrete. Then, for flexural strength total of 36 prism with size of 150mm x 150mm x 750mm were used to determine the flexural strength of concrete when replace with 0%, 5%, 10% and 15% of POC as a replacement of coarse aggregates in concrete. Compressive and flexural strength were conducted at 7 days, 14 days, and 28 days to get the strength of concrete. All of the testing were compared with normal concrete. As the result were obtained, it can concluded that replacement of 10% and 15% POC had a probability to use as a granite replacement in construction industry.